A novel N-heterocycles substituted oseltamivir derivatives as potent inhibitors of influenza virus neuraminidase: discovery, synthesis and biological evaluation - Jiwei Zhang; Chuanfeng Liu; Ruifang Jia; Xujie Zhang; Jian Zhang; Chiara Bertagnin; Anna Bonomini; Laura Guizzo; Yuanmin Jiang; Huinan Jia; Shuzhen Jia; Xiuli Ma; et al. (Taylor & Francis Group, 2023)
Our previous studies have shown that the introduction of structurally diverse benzyl side chains at the C5-NH2 position of oseltamivir to occupy 150-cavity contributes to the binding affinity with neuraminidase and anti-influenza activity. To obtain broad-spectrum neuraminidase inhibitors, we designed and synthesised a series of novel oseltamivir derivatives bearing different N-heterocycles substituents that have been proved to induce opening of the 150-loop of group-2 neuraminidases. Among them, compound 6k bearing 4-((r)-2-methylpyrrolidin-1-yl) benzyl group exhibited antiviral activities similar to or weaker than those of oseltamivir carboxylate against H1N1, H3N2, H5N1, H5N6 and H5N1-H274Y mutant neuraminidases. More encouragingly, 6k displayed nearly 3-fold activity enhancement against H3N2 virus over oseltamivir carboxylate and 2-fold activity enhancement over zanamivir. Molecular docking studies provided insights into the explanation of its broad-spectrum potency against wild-type neuraminidases. Overall, as a promising lead compound, 6k deserves further optimisation by fully considering the ligand induced flexibility of the 150-loop.